Emigration state encounters: The everyday material life of a diaspora technology. (January 2019) - Williams, Philippa
Abstract: Scholars of diaspora studies argue that we need to recognise the emigration state as an ordinary feature of geopolitics rather than conceptualising 'the emigrant state' and consequentially 'the diaspora' as something peculiar and apart from the state. Yet everyday encounters between emigrants and the emigration state have been relatively under researched. This article responds to that blind spot by bringing together scholarship on diaspora studies, state-society relations and the material and affective dimensions of bureaucracy to examine the everyday life of a diaspora technology. More specifically, it examines how Indian emigrants encounter the emigrant state, through the lens of India's 'Overseas Citizen of India' (OCI) card. The OCI was publicly announced as 'dual citizenship' and represented a new category of legal subject abroad. Whilst scholars including geographers have critiqued the exclusive construction of OCI and questioned the extent to which it represents a form of citizenship at all, very little research has engaged with the mundane material and emotional dimensions of this policy. The study draws on interviews with Indian emigrants and their descendants in Greater London, as well as an examination of immigration/emigration website forums and blogs, online petitions and the Government of India's (GoI) paper trail relating to this diaspora strategy. Since its inception, the OCI card has been characterised by ambiguities and alterations concerning the meaning of citizenship and eligibility criteria. The article's findings illuminate the ongoing interplay between the production of illegibility and legibility by the emigrant state and emigrants. In so doing it examines the individual and collective strategies deployed by emigrants to interpret the rules and make the state legible, assemble proof of eligibility, and negotiate periods of waiting for their application. It also explores the situated material and affective dimensions of these emigrant state encounters in shaping emigrant subjectivities. The article concludes that the requirements of applying for OCI can, in some cases, serve to undermine the Government of India's diaspora strategy to naturalise the links between people, state and nation. Highlights: Documents the everyday and mundane experiences of an emigration state. Reveals the multiple actors and sites of power through which emigration statecraft is (re)produced. Shows how material and affective aspects of state encounters challenged the production of positive emigrant subjectivities. Challenges claims that diaspora technologies successfully make the link between people, state and nation look natural.